Risk of Psychiatric Illness From Advanced Paternal Age Is Not Predominantly From De Novo Mutations. Issue 2 (February 2017) - Gratten, Jacob; Wray, Naomi R.; Peyrot, Wouter J.; McGrath, John J.; Visscher, Peter M.; Goddard, Michael E.
Abstract : (Abstracted from Nat Genet 2016;48:718–724) Epidemiologic studies have reported an increased risk of schizophrenia, autism, and other psychiatric disorders among offspring of older fathers. It is widely assumed that paternal age–related de novo mutations are the primary underlying causal mechanism.